Board gender diversity and corporate green innovation: An industry‐level institutional perspective - Naveed, Khwaja; Khalid, Fahad; Voinea, Cosmina Lelia (Corporate social-responsibility and environmental management, 2023)
This study contributes to the inconclusive literature on the relationship between board gender diversity (BGD) and green innovation (GI). It empirically examines the moderating role of normative, mimetic and coercive pressures in the relationship between BGD and GI, derived from an industry‐specific isomorphic exhibition of institutional theory. Appertaining to A‐share listed firms of China, the findings highlight the moderating effect of masculinity, environmental sensitivity, environmental regulation level and export orientation of an industry on the said relationship. Moreover, the coercive isomorphism exhibits pronounced impact with the intensity of export orientation. However, firms associated with high‐tech industries have not been confirmed for significant effect on the relationship. Thus, the findings imply that the dynamics of the corporate governance and institutional isomorphism in case of BGD and GI relationships, in the organisational field of industry, are likely both pertinent and prevalent. Moreover, the increase in the number of females on the corporate boards could enhance the green performance of a firm, subject to the fulfilment of industry specific boundary conditions, predefined by the unique set of industry specific institutional pressures. These pressures amid affiliation with a specific industry should be evaluated and controlled for, on the bases of coercive, normative, and mimetic isomorphism it hatches, to device an optimum composition of the corporate board.